Improving Voltage Stability in Kurdistan Power System in Areas with Deficit Power Production by Rescheduling the Active Power Based on PSS/E Simulation (Journal of Engineering, 2023)
This paper aims to improve the voltage profile using the Static Synchronous Compensator (STATCOM) in the power system in the Kurdistan Region for all weak buses. Power System Simulation studied it for Engineers (PSS\E) software version 33.0 to apply the Newton-Raphson (NR) method. All bus voltages were recorded and compared with the Kurdistan region grid index (0.95≤V ≤1.05), simulating the power system and finding the optimal size and suitable location of Static Synchronous Compensator (STATCOM)for bus voltage improvement at the weakest buses. It shows that Soran and New Koya substations are the best placement for adding STATCOM with the sizes 20 MVAR and 40 MVAR. After adding STATCOM with the sizes [20MVAR and 40MVAR] at Soran to the test, it is seen that the total average change in voltage profile for the system improved results in about 17.34 % in average per unit change for the 28 weakest buses, which provides a good improvement in stability. Also, the system’s total active power loss reduced from 123.8 MW without STATCOM to 102.8 MW with STATCOM. The results are encouraging for applying the approach to the power system. This approach stands out due to all bus voltages are within acceptable ranges.